Domestic Emissions Trading : Existing and Proposed Schemes - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
This document provides an overview and summary assessment of lessons and insights learned from various existing and presented domestic cap and trade schemes. For each scheme, a set of general characteristics (or issues) is considered. The characteristics (or issues) covered include the following: (i) coverage and scope; (ii) setting a cap; (iii) setting the points of obligation; (iv) allocation of allowances; (v) systems for domestic monitoring, reporting and verification, (MRV) and compliance; (vi) enabling trading and fostering stability; (vii) institutional arrangements, including technical and legal infrastructures; and (viii) use of offsets and linking. The domestic emissions trading schemes (ETS) included in this assessment are the following: (i) European Union (EU) ETS; (ii) New Zealand (NZ) ETS; (iii) United States (U.S.) northeast states regional greenhouse gas initiative (RGGI); (iv) California (Cal) ETS; (v) Australia clean energy future carbon pricing mechanism (Aus CPM); and (vi) Tokyo cap and trade program (C and T).